Viver num corpo estrangeiro: sentidos e significados do ter e ser um corpo oriental para adolescentes nikkeis insatisfeitos com suas fenotipias - Ishimori, Karina Midori (2006)
The purpose of this paper (research) is to analyze how one feels and what it means to be of Asian descent in Brazil for adolescents who are unhappy with their phenotypic characteristics. The fundamental phenotype of having "slanted eyes" denounces one as a foreigner in Brazil aside from the fact that one is indeed Brazilian. In his daily life, the Nikkei adolescent is often reminded of his ethnicity by the majority of the population: he is called Japanese. It is assumed that there is a duality for being and feeling Brazilian or Japanese and this experience, made clear through the physical features (characteristics), incites thoughts that must be more deeply understood. To do so, the history of the Japanese immigration to Brazil was reconstructed until currently to contextualize the conditions (reasons) that made them migrate, the conditions that they found upon arrival, the ancestral culture that was carried with them, and how today they act within Brazilian society. Next, the concepts of ethnic and national identity of Asian adolescent descent in Brazil and the difficulty in establishing a bigger or smaller pattern of integration of such people in the social reality of Brazil were exposed. After that, it was also contextualized the body today, the importance of physical characteristics as a means to differentiate individuals in Brazil, and finally the body in historical and dialectal materialism. The methodological and theoretical suppositions of this research are from socio-historical psychology that is based in the cultural-historical psychology of Vigotski. The data was collected in a private elementary and junior high school that primarily serves the Japanese community in São Paulo. In the first phase, the method used was a questionnaire given to junior high students in their 2nd or 3rd year to get to know the students and then select them. The second phase was comprised of interviews with two Nikkei adolescents who belong to the third generation of Japanese migrants and are between 16 and 17 years old. The analysis of the interviews allowed for the identification of the movement and process of the subjective construction of these adolescents in their bicultural experiences. In this regard, it became clear that they live with a constant feeling of not belonging to neither the Occidental nor the Oriental worlds, which is closely related to the way they define (use) their own bodies.